Improved Vivaldi Antenna with Radiation Pattern Control Features - Delphine Abijuru; M.R. Hamid; Ali N. Obadiah (Universitas Ahmad Dahlan, 2018)
Vivaldi antenna has been considered as a mitigation to the scattering effect of an antenna. However, the current performance of Vivaldi antenna suffers from multipath effect, interfering signals and radiation pattern control. This paper proposed an improved Vivaldi antenna which combined triple radiating slot to enable control of radiation pattern features. This is accomplished by controlling the position of the radiating element through the asymmetric arrangement of ideal switches to steer the beam in three desired-directions. The Using operating frequency lied between 900 MHz and 2.5GHz, the proposed design was fabricated and tested. Depending on the radiating element, the proposed antenna covered about ±90º with an almost equal gain at the three different focal in contrast to ±45º coverage of traditional rectangular microstrip antenna beam. The results satisfied pattern reconfigurability and the proposed design can be very useful for wireless communications where multipath fading problems are frequently encountered.